Nigeria/China Politico-Economic Relations and The Challenges of Economic Development in Nigeria, 2015-2022 (Eurasian Journal of Humanities and Social Sciences, 2024)
The diplomatic ties between Nigeria and the People's Republic of China have extended over six decades, becoming increasingly significant as Nigeria navigated the international backlash against its military regimes from the 1970s through 1998. As China's economy burgeoned, driven by a voracious need for oil and petroleum, Nigeria emerged as a key partner, supplying these crucial resources. In return, China offered Nigeria substantial support across economic, military, and political spheres, cementing a formidable bilateral relationship. Despite the flourishing ties, Nigeria's economic interactions with China were impeded by an underdeveloped industrial infrastructure, a longstanding obstacle to Nigeria's economic progress. Successive Nigerian administrations have endeavoured to overcome these challenges. The research under review focused on the politico-economic dynamics between China and Nigeria from 2015 to 2022, analysing them through the lenses of interdependency and unequal exchange theories. Employing a historical and descriptive methodology, the study harnessed secondary data from diverse sources including books, newspapers, digital platforms, periodicals, conference proceedings, unpublished reports, government documents, magazines, and academic journals, all analysed via content analysis. The findings highlighted that the relationship has substantially benefited Nigeria, bringing crucial development aid and investments that have catalysed economic growth. Chinese investments, in particular, have been instrumental in advancing Nigeria’s development agenda, while the influx of Chinese tourists has notably boosted national revenue. Nevertheless, the relationship has faced challenges such as corruption and governance opacity. Given the historical benefits of their economic collaboration, it is recommended that both nations further enhance their partnership through additional Memorandums of Understanding (MoUs) and investments in energy projects, continuing to build on past successes for mutual advantage